Cavitation-enabled rapid and tunable evolution of high-χN micelles as templates for ordered mesoporous oxides. Issue 4 (31st October 2016) - Lokupitiya, Hasala N.; Stefik, Morgan
Abstract : The kinetic entrapment of block copolymer micelles is unlocked with the power of sonication. Abstract : The kinetic-entrapment of block copolymer micelles enables size-persistence, however tuning micelle sizes under such conditions remains challenging. Agitation-induced chain exchange via vortexing is limited by the production of solution–air interfaces. Here, we use ultrasonic cavitation for rapid interface production that accelerates micelle growth by an order of magnitude over vortexing.